(untitled) (The Pakistan Development Review, 1988)
In the realm of monetary economics, the question of the appropriate definition of money is both crucial and controversial. Various definitions of money offered by monetary economists differ widely. While narrowly defined money consists of currency and demand deposits only. other broader definitions of money include a host of other assets as well. The choice of the most appropriate monetary aggregate is an empirical issue and needs to be settled empirically. In the literature a number of methods are available for defining money empirically. To mention only two of them, Meltzer (1963) and Laidler (1966) consider that definition o f money the most appropriate which gives the most stable demand function for money while Chetty (1969), Moroney and Wilberatte (1976), Boughton (1981) and Husted and Rush (1984) infer their definition of money on the basis of the degree of substitutability between narrowly defined money and other financial assets. Although the two methods are closely linked, the latter has the advantage of providing a direct measure of the degree of substitutability between various financial assets and also allows for defining money as a sort of weighted average of these assets based on this substitutability rather than a simple-sum aggregation.